2019
DOI: 10.1055/a-0898-3357
|View full text |Cite
|
Sign up to set email alerts
|

Over-the-scope clip in peptic ulcer bleeding: clinical success in primary and secondary treatment and factors associated with treatment failure

Abstract: Background and study aims It is unclear if the clinical success rate of the over-the-scope-clip (OTSC) in peptic ulcer bleeding (PUB) is comparable when it is used in the first- or in the second-line of treatment. Patients and methods Data on endoscopic treatment (first- vs. second-line) in PUB with OTSC and clinical data were analyzed. The primary outcome was the clinical success of hemostasis, defined as the absence of recurrent bleeding or further intervention. Secondary outcomes were factors ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Of these, 983 studies were excluded according to the predefined criteria and 49 studies were reviewed the full-text. Final literature search and selection according to the inclusion and exclusion criteria yielded 16 studies about OTSC system treatment for UNVGIB [1113, 1628]. Figure 1 showed the search and selection process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 983 studies were excluded according to the predefined criteria and 49 studies were reviewed the full-text. Final literature search and selection according to the inclusion and exclusion criteria yielded 16 studies about OTSC system treatment for UNVGIB [1113, 1628]. Figure 1 showed the search and selection process.…”
Section: Resultsmentioning
confidence: 99%
“…Seven of 16 studies in our systematic review reported the reasons for OTSC treatment failure: 1) delayed closure of OTSC occurring in lesions with large caliber artery and those with deep fibrotic base; 2) shallow placement of OTSC resulting from inadequate suction or premature clip deployment; and 3) misplacement of OTSC because of poor visualization, difficult anatomy, and unstable endoscope position [11, 12, 18, 22, 23, 27, 28]. These failure causes of OTSC above may enlighten its further application in future.…”
Section: Discussionmentioning
confidence: 99%
“…Publication bias was assessed via visual inspection of the funnel plot and Egger's test, the P value of greater than 0.05 WAS CONSIDERED TO NO PUBLICATION BIAS [11]. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. 24.5%, P = 0.177).…”
Section: Discussionmentioning
confidence: 99%
“…Although this data was surprising, only 3.9% patient died related to OTSC system application failure and most of these patients died due to fatal comorbidity. Gölder S. et al deemed that in case of severe recurrent bleeding, the bleeding source could be controlled by endoscopic treatment, but the patient refused any further therapy and died, which was one of the reasons for the high mortality [27].…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 983 studies were excluded according to the predefined criteria and 49 studies were reviewed the full-text. Final literature search and selection according to the inclusion and exclusion criteria yielded 16 studies about OTSC system treatment for UNVGIB [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Figure 1 showed the search and selection process.…”
Section: Included Studiesmentioning
confidence: 99%